Liming of acidified lakes in southwestern Sweden: short-term effects on waterbird densities - Eriksson, Mats O G (Wildfowl, 1987)
Densities of two piscivorous birds, Gavia arctica and Mergus merganser, and three non-piscivorous ducks, Anas plathyrhynchos, A. crecca and Bucephala clangula, were investigated in eight oligotrophic and acidified lakes in spring-early summer 1983, before liming, and again in 1985, after liming. Simultaneously, six control lakes, not limed, were investigated. Average fish density increased and water transparency decreased in the limed lakes, while these parameters remained unchanged in the control lakes. Densities of birds were not affected by liming in itself; although there were significant changes in the limed lakes, similar trends were recorded in the control lakes.